The cabin ebook - Preston, Natasha (2016)
A New York Times Bestseller! There may only be one killer, but no one is innocent in this thriller from Natasha Preston, the #1 New York Times bestselling author of THE CELLAR! A weekend partying at a remote cabin is just what Mackenzie needs. She can't wait to let loose with her friends. But a crazy night of fun leaves two of them dead—murdered. With no signs of a forced entry or struggle, suspicion turns to the five survivors. Someone isn't telling the truth. And Mackenzie's first mistake? Assuming the killing is over... Teen thrillers also by Natasha Preston: The Cellar Awake You Will Be Mine The Lost The Twin